ANALISIS KIMIA DAUN PINUS DAN PEMANFAATANNYA - Bambang Wiyono; Abdul Hakim Lukman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
At present, pine needles have no commercial value. The needles are fire hazard to both natural and plantation grown trees when they accumulate on the ground, couple with inhibition of the growth of the surrounding trees. The research purpose is to determine chemical component of pine needles of three pine i.e Pinus merkusii, P. caribaea, and P. insularis. This endeavor is conducted to explore a wider of such material.The results indicated that the moisture content of P. merkusii, P. caribaea, and P. insularis needles were 4.69 %,3.54 %, and 14.79 % respectively; cellulose content being 12.31 %, 17.19 %, and 18.54 %; lignin content 29.46%,39.54, and 26.65 %; pentosan content 7.04 %, 5. 78 %, and 12.11 %; ash content 3.06 %, 2.40 %, and 7.30 %; silica content 0.44 %, 0.48 %, and 0.19 %; acidity 5.32, 5.33, and 6.15; solubility in cold water 23.38 %, 23.09 %, and 17.84 %; solubility in hot water 26.51 %, 29.62 %, and 17.82 %; solubility in alcohol-benzene (1 : 2) 19.30 %, 19.14 %, and 11.08 %. Based on this component, the pine needles may be utilized as sources of raw materail for production of glucose, fructose, ethanol, ethylene, pine needle oil for pharmaceutical and perfumery industries, etc. The needles can also be used as raw material for gasification and anaerobic fermentation processes for energy production.